2019
DOI: 10.1007/s11104-019-04348-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drought and intercropping on chicory nutrient uptake from below 2 m studied in a multiple tracer setup

Abstract: Aims We tested if chicory acquires nutrients from soil layers down to 3.5 m depth and whether the deep nutrient uptake increases as a result of drought or intercropping with ryegrass and black medic. We also tested whether application of the trace elements Cs, Li, Rb, Sr and Se, as tracers, result in similar uptake rates. Methods The methodological tests were carried out in a pilot experiment where the tracers were applied to 1 m depth in lucerne and red beet grown in tube rhizotrons. The dynamics of deep nutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The use of tracers allows us to assay where roots are actively capturing resources in soil. Careful tracer application in controlled studies or in the semifield RadiMax facility, coupled with minirhizotron imaging, shows that there is potential for the use of 15 N as a tracer for measuring root depth, but tracer use has been limited in field studies in relation to root depth (Chen et al., 2019; Hoekstra et al., 2014; Rasmussen et al., 2020; Saengwilai, Nord, et al., 2014; Saengwilai, Tian, et al., 2014; Svane et al., 2019; Wacker et al., 2022). Here, we used Sr as a tracer in both greenhouse and field studies and found strong correlations with root growth, especially in greenhouse studies, with leaf Sr content correlating strongly with root length (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of tracers allows us to assay where roots are actively capturing resources in soil. Careful tracer application in controlled studies or in the semifield RadiMax facility, coupled with minirhizotron imaging, shows that there is potential for the use of 15 N as a tracer for measuring root depth, but tracer use has been limited in field studies in relation to root depth (Chen et al., 2019; Hoekstra et al., 2014; Rasmussen et al., 2020; Saengwilai, Nord, et al., 2014; Saengwilai, Tian, et al., 2014; Svane et al., 2019; Wacker et al., 2022). Here, we used Sr as a tracer in both greenhouse and field studies and found strong correlations with root growth, especially in greenhouse studies, with leaf Sr content correlating strongly with root length (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used Sr as a tracer in both greenhouse and field studies and found strong correlations with root growth, especially in greenhouse studies, with leaf Sr content correlating strongly with root length (Figures 4 and 5). Though the use of Sr as a tracer is not new (Han et al., 2020; Hoekstra et al., 2014; Rasmussen et al., 2020), our ability to measure Sr content over time with XRF allows for the tracking of leaf accumulation nondestructively and quickly. Compared to tissue analysis by ICP‐OES or ICP‐MS or measurement of isotopes, XRF is much faster and cheaper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to previous findings by Vandoorne et al (2012) and Hashemian et al (2015), showing that moisture level of different soil layers is a key factor which affect root water uptake distribution. However, with a similar experimental setup, Rasmussen et al (2020a) concluded that chicory failed in compensating water uptake from deeper soil layers. They suggested that the high hydraulic resistance and drought-induced stomatal closure might reduce root water uptake and plant water demand, leading to the failure of compensation (Rasmussen et al 2020b).…”
Section: Effect Of N and Water Supply On Root Growthmentioning
confidence: 95%
“…We photographed the roots on 21 June and 18 July 2016 and on 6 July, 16 August and 12 September 2017, corresponding to the time of drought initiation in the DS treatment, 2 H tracer injection (see below) and for 2017, harvest. In 2017, harvest was postponed until 20 days after the 2 H tracer-experiment, due to measurements of nutrient uptake later in the season (Rasmussen et al 2019) We recorded the roots using the line intersects method (Newman 1966) modified to grid lines (Marsh 1971;Tennant 1975) to calculate root intensity, which is the number of root intersections m −1 grid line in each panel (Thorup- Kristensen 2001). To make the counting process more effective we adjusted the grid size to the number of roots, i.e.…”
Section: Root Measurementsmentioning
confidence: 99%